EFFORTS TO IMPROVE LEARNING OUTCOMES IN CIVIC EDUCATION THROUGH THE ‘TALKING STICK’ COOPERATIVE LEARNING MODEL AMONG YEAR 5 PUPILS AT STATE PRIMARY SCHOOL 068003 MEDAN TUNTUNGAN - Darinda Sofia Tanjung; Agnes Girl Ekape Sebayang; Tri Ulina Br Tarigan; Redi Antara Sinaga; Sintia Amelia Sipayung (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to improve learning outcomes in Civic Education (PKN) on the topics of the administrative structure of regencies and cities and appropriate behaviour within the regency and city environment through the application of the ‘Talking Stick’ cooperative learning model to Year 5 pupils at State Primary School 068003, Medan Tuntungan. This study is a Classroom Action Research (PTK) conducted in two cycles, comprising the stages of planning, implementation, observation and reflection. The research sample comprised 26 pupils. Data were collected through learning outcome tests, observation sheets for teacher and pupil activities, and documentation. The research results indicated a significant improvement: the average pupil score on the pre-test was 55.19, rising to 67.69 in Cycle I, and reaching 94.61 in Cycle II. The rate of mastery of the subject matter also increased from 30.77 per cent in the pre-test to 65.38 per cent in Cycle I, and reached 100 per cent in Cycle II. It was concluded that the application of the Talking Stick model was effective in enhancing student engagement and learning outcomes in Civic Education.